MOTIF BATIK KERATON YOGYAKARTA SEBAGAI SUMBER INOVASI PERHIASAN KOTAGEDE - Pandansari Kusumo (Institut Seni Indonesia Yogyakarta, 2013)
The research aim is to create an innovative, creative and unique jewelry based on batikpattern of Kraton of Yogyakarta. The output in the first year are documentation of geometric,non geometric pattern and innovative jewelry design as the results of batik pattern of Kraton ofYogyakarta and silver jewelry using Kotagede’s own technique.Method used on this research namely library method, observation, interview andanalysis of qualitative data which represented descriptively as well as experimentation usingsome sketches. We also apply some possibility using alternative material such as semi preciousstone, shell and pearl. Moreover the benefit expected from this research is to endorse thecreative industry in Indonesia, especially to foster the jewelry production at Kotagede as thesilver center, that no longer active due to some barriers, such as unattractive design.Some sketches as the result of experimentation and chosen design will be produced inthe second year. Keywords: pattern, batik, Yogyakarta, jewelry, Kotagede